Olfactory impairment in COVID-19: Two methods for the assessment of olfactory function. Issue 3 (March 2023) - Tao, Anzhou; Shi, Leyang; Wang, Yuan; Duo, Zefen; Zhao, Xianglian; Mao, Haiting; Guo, Jingxin; Lei, Jia; Bao, Yingsheng; Chen, Geng; Cao, Xianbao; Zhang, Jinqian
Abstract: Background: Olfactory impairment is a major symptom of COVID-19. Is it necessary for COVID-19 patients to perform the detection of olfactory function, even how to select the olfactory psychophysical assessment tool. Methods: Patients infected with SARS-CoV-2 Delta variant were firstly taken into three categories (mild, moderate, and severe) according to the clinical classification. The Odor Stick Identification Test for the Japanese (OSIT-J) and the Simple Olfactory Test were used to assess olfactory function. Moreover, these patients were divided into three groups based on the results of the olfactory degree (euosmia, hyposmia, and dysosmia), too. The statistical analysis of the correlations between olfaction and clinical characteristics of patients were performed. Results: Our study demonstrated that the elderly men of Han were more susceptible to infected SARS-CoV-2, the clinical symptoms of the COVID-19 patients showed a clear correspondence with the disease type and the degree of olfactory disturbance. Whether or not to vaccinate and whether to complete the whole course of vaccination was closely related to the patient's condition. OSIT-J Test and Simple Test were consistent in our work, indicating that olfactory grading would worsen with the aggravation of symptoms. Furthermore, the OSIT-J method maybe better than Simple Olfactory Test. Conclusion: The vaccination has an important protective effect on the general population, and vaccination should be vigorously promoted. Moreover, it is necessary for COVID-19 patients to perform the detection of olfactory function, and the easier, faster and less expensive method for determination of olfactory function should be utilized to COVID-19 patients as the vital physical examination.